Cardiovascular and neuropsychiatric risks of varenicline and bupropion in smokers with chronic obstructive pulmonary disease. Issue 10 (4th May 2017) - Kotz, Daniel; Viechtbauer, Wolfgang; Simpson, Colin R; van Schayck, Onno C P; West, Robert; Sheikh, Aziz
Abstract : Background: Varenicline and bupropion are effective smoking cessation treatments, but there are concerns about their safety in smokers with COPD. Objective: To investigate whether varenicline and bupropion are associated with serious adverse cardiovascular and neuropsychiatric events in smokers with COPD. Methods: In a retrospective cohort study, we used data from 14 350 patients with COPD included in the QResearch database, which holds data from 753 National Health Service general practices across England. We identified patients with COPD who received a prescription of nicotine replacement therapy (NRT; N=10 426; reference group), bupropion (N=350) or varenicline (N=3574) in the period between January 2007 and June 2012. Patients were followed up for 6 months to compare incident cardiovascular (ie, ischaemic heart disease, stroke, heart failure, peripheral vascular disease and cardiac arrhythmias) and neuropsychiatric (ie, depression and self-harm) events using Cox proportional hazards models, adjusted for potential confounders. Propensity score analysis was used as an additional approach to account for potential confounding by indication. We also modelled the effects of possible unmeasured confounders. Results: Neither bupropion nor varenicline showed an increased risk of adverse events compared with NRT. Varenicline was associated with a significantly reduced risk of heart failure (HR=0.56, 95% CI 0.34 to 0.92) and depression (HR=0.73, 95% CI 0.61 to 0.86). Similar results were obtained from the propensity score analysis. Modelling of unmeasured confounding provided additional evidence that an increased risk of these adverse events was very unlikely. Conclusion: In smokers with COPD, varenicline and bupropion do not appear to be associated with an increased risk of cardiovascular events, depression or self-harm in comparison with NRT.